Chitosan-Derived Three-Dimensional Porous Graphene for Advanced Supercapacitors - Wang, Chao; Zhong, Guobin; Zhao, Wei; Wu, Shijia; Su, Wei; Wei, Zengfu; Xu, Kaiqi (Frontiers in Energy Research, 2020)
Graphene for energy storage devices suffers from the preparation method and deficient quality, hindering their further widespread application. Here, we report a facile and cost-effective approach to derive three-dimensional porous graphene (3DPG) from biocompatible chitosan for massive production. Taking advantage of the large surface area, excellent electrical conductivity and high electrochemical activity of the 3DPG, an advanced symmetric supercapacitor (3DPG//3DPG SCs) is achieved by coupling two 3DPG electrodes in commercial DLC301 organic electrolyte. The device delivers a remarkable capacitance of 168.9 F g-1 at the scan rate of 10 mV s-1 and displays a superior rate capability, witnessing 81.5% capacitance retention from 10 to 100 mV s-1. Furthermore, the 3DPG//3DPG SCs exhibits prominent cyclic durability, as evidenced by its 96% capacitance after 10,000 cycles. This work might shed light on the probable application of graphene at industrial level for efficient energy storage.